Evaluating remote facilitation intensity for multi-national translation of nurse-initiated stroke protocols (QASC Australasia): a protocol for a cluster randomised controlled trial - Fasugba, O.; Dale, S.; McInnes, E.; Cadilhac, D. A.; Noetel, M.; Coughlan, K.; McElduff, B.; Kim, J.; Langley, T.; Cheung, N. W.; Hill, K.; Pollnow, V.; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background Facilitated implementation of nurse-initiated protocols to manage fever, hyperglycaemia (sugar) and swallowing difficulties (FeSS Protocols) in 19 Australian stroke units resulted in reduced death and dependency for stroke patients. However, a significant gap remains in translating this evidence-based care bundle protocol into standard practice in Australia and New Zealand. Facilitation is a key component for increasing implementation. However, its contribution to evidence translation initiatives requires further investigation. We aim to evaluate two levels of intensity of external remote facilitation as part of a multifaceted intervention to improve FeSS Protocol uptake and quality of care for patients with stroke in Australian and New Zealand acute care hospitals. Methods A three-arm cluster randomised controlled trial with a process evaluation and economic evaluation. Australian and New Zealand hospitals with a stroke unit or service will be recruited and randomised in blocks of five to one of the three study arms—high- or low-intensity external remote facilitation or a no facilitation control group—in a 2:2:1 ratio. The multicomponent implementation strategy will incorporate implementation science frameworks (Theoretical Domains Framework, Capability, Opportunity, Motivation – Behaviour Model and the Consolidated Framework for Implementation Research) and include an online education package, audit and feedback reports, local clinical champions, barrier and enabler assessments, action plans, reminders and external remote facilitation. The primary outcome is implementation effectiveness using a composite measure comprising six monitoring and treatment elements of the FeSS Protocols. Secondary outcome measures are as follows: composite outcome of adherence to each of the combined monitoring and treatment elements for (i) fever (n=5); (ii) hyperglycaemia (n=6); and (iii) swallowing protocols (n=7); adherence to the individual elements that make up each of these protocols; comparison for composite outcomes between (i) metropolitan and rural/remote hospitals; and (ii) stroke units and stroke services. A process evaluation will examine contextual factors influencing intervention uptake. An economic evaluation will describe cost differences relative to each intervention and study outcomes. Discussion We will generate new evidence on the most effective facilitation intensity to support implementation of nurse-initiated stroke protocols nationwide, reducing geographical barriers for those in rural and remote areas. Trial registration ACTRN12622000028707. Registered 14 January, 2022.